2016
DOI: 10.17116/patol201678113-18
|View full text |Cite
|
Sign up to set email alerts
|

Histological hanges in the placenta and vascularization of its villi in early- and late-onset preeclampsia

Abstract: It was determined that there was a preponderance of branching angiogenesis in the preeclamptic chorionic villi and an increase in the number of syncytial nodules and microcysts in the septae in late-onset preeclampsia. Morphometric analysis of immunohistochemical placental specimens established a reduction in the sizes and vascularization indicators of terminal villi that determine the development of placental hypoxia and are more pronounced in cases of early-onset preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…An abnormal immune reaction has been proposed as the cause of extensive perivillous fibrin depositions and chronic intervillositis [23,77]. The predominance of angiogenesis with branching vessels in the placenta of COVID-19-affected women revealed by us can be considered as a compensatory process to increase the area of gas exchange of the villous tree in response to uteroplacental hypoxia caused by maternal SARS-CoV-2 infection, as has been demonstrated in preeclampsia [78]. The key role in the formation of fetoplacental angiogenesis throughout gestation is assigned to the vascular endothelial growth factor (VEGF) and its receptors (VEGFR-1 и VEGFR-2), placental growth factor (PlGF), angiopoietins, and many other growth factors, which are upregulated with low oxygen tension to facilitate the expansion of placental vascular network [79].…”
Section: Discussionmentioning
confidence: 72%
“…An abnormal immune reaction has been proposed as the cause of extensive perivillous fibrin depositions and chronic intervillositis [23,77]. The predominance of angiogenesis with branching vessels in the placenta of COVID-19-affected women revealed by us can be considered as a compensatory process to increase the area of gas exchange of the villous tree in response to uteroplacental hypoxia caused by maternal SARS-CoV-2 infection, as has been demonstrated in preeclampsia [78]. The key role in the formation of fetoplacental angiogenesis throughout gestation is assigned to the vascular endothelial growth factor (VEGF) and its receptors (VEGFR-1 и VEGFR-2), placental growth factor (PlGF), angiopoietins, and many other growth factors, which are upregulated with low oxygen tension to facilitate the expansion of placental vascular network [79].…”
Section: Discussionmentioning
confidence: 72%
“…In preeclampsia, the number of syncytial knots was also increased in observed [7]. At the same time, increased numbers of syncytial knots were significantly more often observed in late-onset preeclampsia compared to early-onset preeclampsia [1].…”
Section: Resultsmentioning
confidence: 83%
“…On the other hand, other investigators reported decreased microvessel counts in PE placentas [7,9,11,31,32] . These studies included population of early onset PE and reported poor fetal outcome with FGR and still birth.…”
Section: Similar To Our Results Sankar Et Al (2012) Andmentioning
confidence: 88%